Landscape, process and power : a re-evaluating traditional environmental knowledge - Heckler, Serena (Studies in environmental anthropology and ethnobiology, 2009)
In recent years, the field of study variously called local, indigenous or traditional environmental knowledge (TEK) has experienced a crisis brought about by the questioning of some of its basic assumptions, for instance that scientific methods can accurately elicit and describe TEK or that incorporating it into development projects will improve the physical, social or economic well-being of marginalized peoples. The contributors to this volume argue that to accurately and appropriately describe TEK, the historical and political forces that have shaped it, as well as people's day-to-day engage.